ANALISIS PEMENUHAN SISTEM TANGGAP DARURAT KEBAKARAN PADA PT. PEMBANGKIT JAWA BALI DI BALIKPAPAN - Maslina, Maslina; Zainul , L.M; Noeryanto, Noeryanto; Lilis Suryanti , Jumdana (IDENTIFIKASI, 2022)
The Java Bali Power Plant in Balikpapan is one of the companies engaged in power plant operation and maintenance services, which have work activities that can trigger hotspots that can cause fires while the process is in progress. Because researchers want to know whether the existing Fire Emergency Response System at PT Pembangkit Jawa Bali is in accordance with existing standards or therefore an analysis of the fire emergency response system that exists in the company is needed. Based on secondary data, at PT Pembangkit Jawa Bali there has been a fire disaster in in 2016 as many as 1 case was only a small fire, a case that occurred at PT Pembangkit Jawa Bali. As a result of the fire incident in several areas, the production time was between 2 days and 5 days, which would reduce the electrical load that should have caused power outages in various areas. Damage to machines that must be repaired are replaced with new machines, as well as material losses that reach hundreds of millions. From the results of field observations and data from primary secondary data, it shows the results of the study so that the average Emergency Response System Fulfillment Rate is 89%. So it can be concluded that the fulfillment of the fire emergency response system at PT Pembangkit Jawa Bali in Balikpapan has an average fulfillment value of 81%. So the level of fulfillment is included in the "GOOD" classification according to the fire audit table of the Research and Development Center of the Ministry of Public Works Pd-T-11-2005-C which means all components are based on the fulfillment of the fire emergency response system as needed, but there are several criteria that are lacking.